Effect of Task Oriented Training on Gross Motor Dysfunction for Children with Cerebral Palsy： A Meta-Analysis - LI Yang; CHEN Ying; ZHU Xiangyu; SHI Jiehong; FENG Yuan; WU Wenlei; FU Ruochen (康复学报)
ObjectiveTo evaluate the effect of task oriented training (TOT) on gross motor dysfunction for children with cerebral palsy (CP) by meta analysis.MethodsThe databases of PubMed, Embase, Cochrane Library, Web of Science, CINAHL, ProQuest, CNKI, VIP, Wanfang Data, CBMdisc and Electronic literature search database of Peking University Health Science Center were searched from inception to March 10, 2022 for randomized controlled trials (RCTs) on TOT for children with CP by manual and computer search. The Cochrane Collaboration's tool for assessing risk of bias was used to evaluate the qualities of included studies, and relevant data were extracted. Outcome measures mainly included gross motor function measure (GMFM) score, Berg balance scale (BBS) score, pediatric evaluation of disability inventory (PEDI) score, timed "up and go" (TUG). RevMan 5.4 software was used for meta-analysis. Continuous data were described by mean difference (MD), standardized mean difference (SMD) and 95% confidence interval (CI), and I 2 and P value were used to evaluate heterogeneity. The fixed effects model was used when the included studies were homogeneous (I 2≤50%, P≥0.1) , while the random effects model was used for analysis when the included studies were heterogeneous (I 2>50%, P<0.1).ResultsA total of 22 RCTs with 1 159 cases were included, with 579 cases in the control group and 580 cases in the experimental group. Meta-analysis results showed that, compared with the control group, the GMFM scale standing score in the experimental group was higher [SMD=0.78, 95% CI (0.59, 0.98), P<0.000 01], walking, running and jumping scores was higher [SMD=4.05, 95% CI (2.06, 6.05), P<0.000 01], GMFM scale overall score was higher [SMD=10.23, 95% CI (7.00, 13.46), P<0.000 01], PEDI score was higher [SMD=6.87, 95% CI (4.19, 9.54), P<0.000 01], TUG test time was shorter [SMD=-3.17, 95% CI (-4.84, -1.49), P=0.000 2], and BBS score was higher [SMD=5.26, 95% CI (4.05, 6.46), P<0.000 01].ConclusionTask oriented training can effectively improve the gross motor function (such as walking, running, jumping, etc.) of children with cerebral palsy, shorten the TUG test time, and improve their balance function and activities of daily living.